Numerical investigation of reactive powder concrete reinforced with steel wire mesh against high-velocity projectile penetration - Liu, J.; Wu, C.; Li, Jun; Su, Y.; Chen, X. (Elsevier BV, 2018)
© 2018 Elsevier Ltd This paper numerically investigates the effects of steel wire mesh reinforcement on reactive powder concrete (RPC) targets subjected to high-velocity projectile penetration. A numerical model based on a computer program called LS-DYNA was validated with experimental data concerning the depth of penetration (DOP) and crater diameter of reinforced RPC targets. With the validated numerical model, a series of parametric studies are conducted to investigate how the variables of steel wire mesh reinforcement such as the configuration of steel wire meshes, number of layers, space between layers, space between steel wires per layer, as well as the diameter and tensile strength of steel wires affect DOP and crater diameter of reinforced RPC targets. Moreover, the energy evolution of projectile and steel wire meshes during the projectile penetration is discussed. Based on the results of parametric studies, an empirical equation derived from the simulation data is proposed to predict DOP of reinforced RPC targets.